2018
DOI: 10.1186/s10020-018-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus downregulates vitamin D receptor levels in hepatoma cell lines, thereby preventing vitamin D-dependent inhibition of viral transcription and production

Abstract: BackgroundVitamin D is a key immune-modulator that plays a role in the innate and adaptive immune systems. Certain pathogens impair the immune defense by downregulating the vitamin D receptor (VDR) pathway. Low serum levels of vitamin D are associated with increased hepatitis B virus (HBV) replication. Our study aimed to assess the in-vitro relationship between HBV production and Vitamin D signaling pathway and to explore the associated mechanism(s).MethodsHBV transcription and replication was evaluated by qRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The immunomodulatory role of vitamin D in viral infections is more complex and appears to vary based on the nature of pathogen and the type of immune function that is primarily responsible for disease resolution . In addition, the anti‐viral effects of vitamin D appears to be transient, ranging from differentially regulated viral immune responses to regulation of viral pathogenesis either directly or indirectly (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The immunomodulatory role of vitamin D in viral infections is more complex and appears to vary based on the nature of pathogen and the type of immune function that is primarily responsible for disease resolution . In addition, the anti‐viral effects of vitamin D appears to be transient, ranging from differentially regulated viral immune responses to regulation of viral pathogenesis either directly or indirectly (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, reduced VD levels were associated with the clinical progression of liver cirrhosis and adverse clinical outcomes [117]. In line with this clinical evidence, the downregulation of VDR expression in HBV-transfected cells caused an increase in HBV transcription and translation [118]. Effective antiviral therapy, in contrast, restored VD to normal levels in HBV patients [119].…”
Section: Effect Of Vd On Hbv Infection Immune Response Pathogenesismentioning
confidence: 78%
“…Some investigations have indicated that serum 25(OH)D level is negatively correlated with HBV load, and low 25(OH)D level is associated with HBV genotype B, HBsAg, and HBeAg[ 11 , 14 ]. Other studies have shown inconsistent results[ 8 , 10 , 12 ]. In the present study, 25(OH)D was not correlated with HBV DNA in patients with CHB, and serum levels of 25(OH)D did not differ significantly between patients with or without HBeAg, patients with HBV genotype B or C, patients with or without HBsAg, and patients with or without detectable HBV DNA.…”
Section: Discussionmentioning
confidence: 96%
“…Combination of the active form of vitamin D and vitamin D receptor (VDR) may inhibit the proliferation of Th1 cells and the release of cytokines and concurrently activate Th2 cells, thus regulating the immune response. However, HBV-transfected cells downregulate VDR expression, thereby preventing vitamin D from inhibiting transcription and translation of HBV in vitro , and HBV might use this mechanism to avoid the immune system[ 8 ]. Therefore, it is believed that vitamin D is closely linked to hepatitis B.…”
Section: Introductionmentioning
confidence: 99%